Some considerations regarding the problem of multidimensional utility - Martin Binder (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
The concept of utility is often used in ambiguous ways in economics, from having substantive psychological connotations to being a formal placeholder representing a person's preferences. In the accounts of the early utilitarians, it was a multidimensional measure that has been condensed during the marginalist revolution into the unidimensional measure we know today. But can we compare different pleasures? This paper assesses the evidence from psychology and neurosciences on how to best conceive of utility. It turns out that empirical evidence does not favor a view of multidimensional utility. This does not eliminate the possibility to make a normative argument supporting a multidimensional notion of utility.
Keywords: D87; B41; B12; 330; utility; pleasures; neuroeconomics; multidimensionality of utility; Nutzen; Präferenztheorie; Psychologie; Neuroökonomie